The women : [compact disc, unabridged] : a novel - Boyle, T. Coraghessan (Blackstone Audio, 2009)
Using Frank Lloyd Wright as his muse, T.C. Boyle presents a novel based on the great American architect and the four distinct women that permeated his life, career, and heart.